2016
DOI: 10.1891/0886-6708.vv-d-13-00188
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Victimization During Incarceration: Relations to Psychosocial Adjustment During Reentry to the Community

Abstract: We surveyed male ex-offenders (N = 100) about their experiences during and prior to incarceration to assess the role of these factors in psychosocial adjustment postrelease. Participants completed measures of preincarceration mental health problems and severe victimization and feelings of safety during incarceration; they also self-reported emotional distress, antisocial behavior, and posttraumatic stress (PTS). Moderator analyses of PTS outcomes revealed two key interactions between preincarceration mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Previous research has confirmed the relevance of vicarious victimization to explain recidivism and well-being after serving a prison sentence (Daquin et al, 2016;Listwan, Colvin, Hanley, & Flannery, 2010;Listwan et al, 2011;Schappell, Docherty, & Boxer, 2016). However taking into account prison research that shows that the harshness of the prison experience is due both to the relationships among prisoners and the relationships between prisoners and staff (Bottoms, 1999;Liebling, 2004), we elaborated a scale of "negative prison environment" that includes both the perception of victimization among prisoners and the perception of unfair treatment by staff.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research has confirmed the relevance of vicarious victimization to explain recidivism and well-being after serving a prison sentence (Daquin et al, 2016;Listwan, Colvin, Hanley, & Flannery, 2010;Listwan et al, 2011;Schappell, Docherty, & Boxer, 2016). However taking into account prison research that shows that the harshness of the prison experience is due both to the relationships among prisoners and the relationships between prisoners and staff (Bottoms, 1999;Liebling, 2004), we elaborated a scale of "negative prison environment" that includes both the perception of victimization among prisoners and the perception of unfair treatment by staff.…”
Section: Discussionmentioning
confidence: 87%
“…These findings appear somewhat as a paradox, given the number of studies that indicate the high prevalence of the phenomenon (Dias et al, 2019;Wolff et al, 2007) and attest to its negative impact on mental health (Conde et al, 2019b;Schappel et al, 2016) and social reintegration (Zweig et al, 2015) of prisoners. Given that there are specific studies and exclusively dedicated to the prevalence and impact of the phenomenon of prison victimization, the absence of studies on specific measures or intervention proposals for prison victim is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also pointed out the negative effects of this victimization, namely on the psychological stability and mental health of prisoners (Conde et al, 2019b;Schappel et al, 2016) as well as in terms of criminal recidivism (Boxer et al, 2009). Several studies reveal its association with problems of psychological adjustment, both during imprisonment and after return to freedom (Boxer et al, 2009;Listwan et al, 2012;Zweig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying a trauma-informed lens to experiences of incarceration provides important insight for understanding causal relationships between incarceration and mental and behavioral health ( 10 , 11 ). Rates of potentially traumatic events (PTEs) during incarceration have been reported as high as 96.8% among incarcerated people ( 12 ). One study found that 89% of individuals witnessed or experienced an assault while incarcerated ( 13 ).…”
Section: Introductionmentioning
confidence: 99%